The welfare impact of parallel imports: A structural approach applied to the German market for oral anti-diabetics - Tomaso Duso; Annika Herr; Moritz Suppliet (Heinrich Heine University Düsseldorf, Düsseldorf Institute for Competition Economics (DICE), 2014)
We investigate the welfare impact of parallel imports using a large panel data set containing monthly information on sales, ex-factory prices, and further product characteristics for all 700 anti-diabetic drugs sold in Germany between 2004 and 2010. We estimate a two-stage nested logit model of demand and, based on an oligopolistic model of multi- product firms, we then recover the marginal costs and markups. We finally evaluate the effect of the parallel imports' policy by calculating a counter-factual scenario without parallel trade. According to our estimates, parallel imports reduce the prices for patented drugs by 11% and do not have a significant effect on prices for generic drugs. This amounts to an increase in the demand-side surplus by e19 million per year (or e130 million in total) which is relatively small compared to the average annual market size of around e227 million based on ex-factory prices. The variable profits for the manufacturers of original drugs from the German market are reduced by e18 million (or 37%) per year when parallel trade is allowed, yet only one third of this difference is appropriated by the importers.
Keywords: I11; I18; L13; L51; 330; parallel imports; pharmaceuticals; structural models; anti-diabetic drugs